2018
DOI: 10.1101/324541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of algorithms for automated detection of cervical pre-cancers with a low-cost, point-of-care, Pocket colposcope

Abstract: Goal: In this work, we propose methods for (1) automatic feature extraction and classification for acetic acid and Lugol's iodine cervigrams and (2) methods for combining features/diagnosis of different contrasts in cervigrams for improved performance. Methods: We developed algorithms to pre-process pathology-labeled cervigrams and to extract simple but powerful color and textural-based features. The features were used to train a support vector machine model to classify cervigrams based on corresponding pathol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…First, the number of patients and images included in this study was the largest from all colposcopic machine learning models created till date. Previous studies have only included 51–158 subjects with 170–485 colposcopic images 22 , 23 , 35 , 36 , whereas our study included 791 subjects with 791 colposcopic images. Second, the colposcopic images were obtained from three medical centers (the Kangnam Sacred Heart Hospital, Dongtan Sacred Heart Hospital, and Seoul St. Mary’s Hospital).…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of patients and images included in this study was the largest from all colposcopic machine learning models created till date. Previous studies have only included 51–158 subjects with 170–485 colposcopic images 22 , 23 , 35 , 36 , whereas our study included 791 subjects with 791 colposcopic images. Second, the colposcopic images were obtained from three medical centers (the Kangnam Sacred Heart Hospital, Dongtan Sacred Heart Hospital, and Seoul St. Mary’s Hospital).…”
Section: Discussionmentioning
confidence: 99%
“…Early in 2009, Acosta et al 21 used K-NN algorithm to automatically distinguish normal and abnormal cervical tissue in aceto-white pattern, and gained a sensitivity of 71% and the specificity of 59%. Years later, Asiedu et al 22 achieved the sensitivity, specificity, and accuracy of 81.3%, 78.6%, and 80.0% to distinguish CIN+ and benign tissues apart. Liming Hu et al 23 established a cohort and followed up for 7 years, using images shot by cervicography, to train and validate deep learning algorithm and gained higher accuracy compared to pap smear.…”
mentioning
confidence: 99%
“…Kim et al trained a support vector machine (SVM) with 2000 cervical images and achieved the sensitivity and specificity of 75% for CIN2+ and normal/CIN1 classification [19]. Asiedu et al trained and validated a SVM model with 134 patients and achieved 80% accuracy, 81.3% sensitivity, and 78.6% specificity for detecting CIN1+ against normal/benign tissues [20]. Miyagi et al trained and validated AI classifier by using 310 images, which showed a high accuracy of 82.3%, sensitivity of 80%, and specificity of 88.2% for the classification of CIN1 and CIN2+ [21].…”
Section: The Advancements In Computer Algorithms Applying To Cervicalmentioning
confidence: 99%